A Study on the Factors Influencing Sunlight in Block Layout: A Case Study of Barcelona Sample - Yunan Zhang; Wenxuan Chen; Kaidi Zhu (Buildings)
Block layout is the main urban pattern in many city centers in the East and West, and this layout has a long history and will continue to develop in the future. However, there are relatively few studies on the quantitative analysis of this layout, especially its sunlight impact. This study examines the characteristics of the neighborhood-style layout. A sample of the small block dense street network block layout that evolved and developed based on Cerdà’s planned Barcelona was selected. The effects of urban latitude and the angle between the street and north–south are explored on the level of sunlight in the neighborhood space. By using the Ladybug plug-in to simulate the Cerda Barcelona neighborhood model, this study analyzes the quantitative impacts of different geographic latitudes and north–south angle changes on the daylight levels of streets, courtyards, building facades, and ground floor building elevations. The results show that changes in the latitude and north–south angle significantly affect the daylight level of each part of the space in the neighborhood, which provides a quantitative basis for the daylight adaptation analysis. Based on the simulation results, this paper proposes a regression model for the influencing factors of the neighborhood-style layout. The adaptive boundary conditions of this layout in a high-density urban environment are arranged by analyzing the regression model. To a certain extent, this study provides a theoretical basis and corresponding reference for tightening the daylight and environmental health requirements of urban layouts for high-density composite urban development.